An introduction to Bayesian inference in econometrics - Zellner, Arnold (New York : Wiley, 1971)
The purpose of this book is to provide readers with an introduction to Bayesian inference in econometrics. An effort has been made to relate the problems of inference in econometrics to the general problems of inference in science and to indicate how the Bayesian approach relates to general problems of scientific inference in Chapter 1.
Bibliography: p. 415-422.
rpm 13/09/2017
Loans
Keywords: Econometrics; Bayesian statistical decision theory